(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
Introduction: Patola is an important plant drug used in many Ayurvedic medicinal preparations. The source plant of Patola is Trichosanthes cucumerina var. cucumerina, belonging to Cucurbitaceae family, found distributed (growing wild) throughout India especially in Bengal, Gujarat, Konkan, Deccan and Kerala. It is an extensively climbing annual herb with slightly downy or pubescent slender five angular –furrowed stems. It is found climbing over small trees, hedges and suitable supports. The present work is taken up with an objective to standardize Patola with detailed physical and preliminary phytochemical standards. Methods: Samples of Trichosanthes cucumerina var. cucumerina (Patola) was collected from Thellakom, Kottayam district. The plant was properly identified and authenticated by Dept of Botany, University of Kerala. The sample was shade dried and stored in an air tight container. Physicochemical, phytochemical, chromatographic and heavy metal analysis was carried out as per ICMR procedures. Result: On physicochemical evaluation water soluble extractive value was 9.07+ 0.012 and alcohol soluble extractive value was 18.72+ 0.027. Heavy metals copper, cadmium, iron and lead levels were within normal limits. HPTLC was carried out with Toluene: Ethyl acetate: Formic acid as solvent system and 3 spots were obtained. Conclusion: Patola, Trichosanthes cucumerina var. cucumerina, Phytochemicals, HPTLC, AAS.